Reliability of single panoramic radiograph with vertical and horizontal parallax; and intraoral periapical radiograph with Clark's rule compared to computed tomography/surgical exposure in localization of impacted permanent maxillary canine - Vijay Kumar Bokkasam; Sathish Babu Devaki; Ravi Raj Jayam; Pavani Muddepalle; Charitha Marisetty; Abhinaya Reddy Tupalli (Wolters Kluwer Medknow Publications, 2015)
Aim: The aim of the study was to evaluate an accurate, inexpensive and low-radiation conventional radiograph suitable for localization of impacted maxillary permanent canine. Materials and Methods: The study comprised 38 subjects in the age group of 13-50 years of both the genders with 50 impacted canines. Panoramic radiographs (OPGs) (on which Chaushu et al. criteria was applied) and intraoral periapical radiographs (IOPARs) (on which Clark's rule was applied) of the subjects were made and the accuracy of the above two radiographic techniques were compared with computed tomography (CT) axial sections or with surgical exposure, which was considered as the standard guide for localization of impacted maxillary permanent canine. The data obtained was tabulated and subjected to statistical analysis using the statistical package for SAS software. Results: Localization of impacted maxillary permanent canine tooth done with SLOB (Same Lingual Opposite Buccal)/Clark's rule technique could predict the bucco-palatal canine impactions in 98% of cases. OPG using differential magnification index could predict location only in 68% of bucco-palatal canine impactions and in 72% based on vertical position. Conclusion: In 68% of cases the bucco-lingual position of the canine in OPG (by magnification index) coincided with the location as per CT/surgical exposure. In 98% of cases localization with SLOB technique coincided with CT/surgical exposure. 72% of cases showed coincidence with vertical position of the canine on OPG with CT/surgical exposure. IOPARs taken with SLOB technique are more accurate than OPGs for localization of impacted permanent maxillary canine teeth.